Effect of Fertilizer SP-36 And Kascing Fertilizer on the Growth of Peanuts (Arachis Hypogaea L) - Sianturi, Tantri; Elli Afrida; Lisdayani; Mukti Hakim (Talenta Publisher, 2024)
Peanut production in Indonesia in 2016 amounted to 570,477 tons and in 2017 decreased by 495,396 tons. One of the important factors in increasing peanut production is fertilization. The application of phosphate fertilizers can also increase crop yields, especially in soils that lack this element. roots and required P. Vermicompost fertilizer contains various nutrients needed by plants such as gibberellins, cytokinins and auxins which play a role in increasing plant height. The purpose of this study was to determine the effect of growth and production of peanuts (Arachis hypogaea L.) on the application of SP 36 fertilizer and vermicompost fertilizer. This study used a factorial randomized block design with factor I giving POC Lamtoro leaves (P) with 4 levels, namely: P0: Control, P1: 200 cc/plant, P2: 300 cc/plant, P3: 400 cc/plant. Factor II Fertilizer application SP 36 (F) with 4 levels, namely: Fo: Control, F1: 25 g/plot, F2: 50 g/plot and F3: 75 g/plot. The results showed that the application of SP 36 fertilizer and the application of vermicompost fertilizer and the interaction of the two factors had no significant effect on the observed parameters of the number of plant branches.